Exogenous aspartic acid alleviates salt stress-induced decline in growth by enhancing antioxidants and compatible solutes while reducing reactive oxygen species in wheat - Sadak, Mervat Sh; Sekara, Agnieszka; Al-ashkar, Ibrahim; Habib-ur-Rahman, Muhammad; Skalicky, Milan; Brestic, Marian; Kumar, Ashwani; Sabagh, Ayman El; Abdelhamid, Magdi T. (Frontiers in Plant Science, 2022)
Natural compounds such as aspartic acid could improve plant tolerance against stress factors. Therefore, a factorial pot trial in a completely randomized design was conducted to examine the potential role of exogenous of aspartic acid in increasing the tolerance of wheat against salt stress. Wheat plants were sown with different levels of salinity (0, 30, or 60 mM NaCl) and were treated with three levels of exogenous application of aspartic acid (Asp) (0, 0.4, 0.6, or 0.8 mM) foliar sprayed twice. Outcomes of the study indicated that salinity stress decreased growth attributes like length of shoot, leaf area, and shoot biomass along with photosynthesis pigments and endogenous indole acetic acid. Total carbohydrates, total flavonoid content, beta carotene, lycopene, and free radical scavenging activity (DPPH%) were reduced due to NaCl stress. However, Asp application enhanced photosynthetic pigments, and endogenous indole acetic acid, consequently improving plant leaf area, leading to higher biomass dry weight either under salt-stressed or non-stressed plants. Exogenous of Asp up-regulated the antioxidant system viz. antioxidant enzymes (superoxide dismutase, peroxidase, catalase, and nitrate reductase), and non-enzymatic antioxidants (ascorbate, glutathione, total phenolic content, total flavonoid content, beta carotene, lycopene) contents resulted in declined accretion of reactive oxygen species (ROS). The decreased ROS in Asp treating plants resulted in reduced hydrogen peroxide, lipid peroxidation (MDA), and aldehyde either under salt or non-salt stress conditions. Moreover, Asp foliar application increased compatible solute accumulation (amino acids, proline, total soluble sugar, and total carbohydrates), and increased radical scavenging activity of DPPH and enzymatic ABTS. Results revealed that 100% of the variation in shoot dry weight (SDW) yield is explicated through the quadratic regression model. With an increase in Asp application level by 1.0 mM, the SDW was projected to upsurge through 956 mg per plant. In the quadratic curve model, if Asp is applied at a level of 0.95 mM, the SDW is probable to be 2.13 g plant-1. It could be concluded that exogenous aspartic acid application mitigated the damage to wheat due to salt stress. Thus, the application of aspartic acid is more possible due to its economic benefits under salt stress.